RehabilitacjaPhysiotherapy after lung transplantation at the Silesian Centre for Heart Diseases, Zabrze – new challenges, new chance for patients - Foik, Joanna; Wojarski, Jacek; Blicharska-Drobny, Beata; Kucewicz-Czech, Ewa; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The aim of the article is to present physiotherapy procedures devised at the Silesian Centre of Heart Diseases in Zabrze, Poland for patients after lung transplantation in the early postoperative period. The authors present physiotherapeutic methods which encompass: maintaining bronchial tree patency, expansion of the transplanted lung, early mobilization of the recipient, and prevention of respiratory system infections, especially in emaciated patients with irreversible lung damage prior to surgery. The authors also present modifications in the rehabilitation process in the case of complications.